Faktor Eksternal yang Mempengaruhi Perkembangan Kepribadian Remaja di Jorong Melayu Palak Lawe Nagari Pasir Talang Kecamatan Sungai Pagu Kabupaten Solok Selatan - -, Nurrahima - (Bimbingan dan Konseling, 2014)
The background of the research is by the teenager who should be entitled unhealthy personality that teens who do not have confidence, adolescents who with drew from the envi roment, the teen against his parents and teens who are not biased to socialize well. This research aims to look at the external factors that influence the development of adolescent personality, factor from the aspects of the family environment (parenting parents), and environmental aspects of society. This research is descriptive gualitative research. This research was carried on using interview with key informants and observations 4 teenager peoples and 5 peoples additional informants from each key informant that teen parents, his sister, his neighbors, and the head of customs for dig deeper into the rules in the Jorong Melayu Palak Lawe Nagari Pasir Talang Kecamatan Sungai Pagu Kabupaten Solok Selatan. The accuracy of this data in the test by doing triangulation of data, from the data was analyzed in three stages: 1) data reduction, 2) presentation of data, 3) inference. The results obtained by the research findings that parenting parents giving freedom to teenagers without any advance directive that make parenting freedom to adolescent withont any advance directives so as to make them the freedom misrepresented, parenting parents were less well to adolescent by implementing regulations certain rules to adolescent without knowing their desires and expectation, parenting parents not liking teenager who do not heed again the norms and rules that apply in the community because they assume the rules mill hamper them in the association, the community environment that is less condive in supporting the development of adolescent personality because people are less concerued about the actions and behavior of teenagers and people who like to mock and also gossiping teenage behavior without reprimanding his actions.